BAMTAARE SA, the first private company licensed to manufacture and distribute Aflasafe SN01 for benefiting Senegal and The Gambia - CGIAR Research Program on Agriculture for Nutrition and Health (2017)
A4NH researchers at IITA developed Aflasafe SN01, an aflatoxin biocontol product for use in Senegal and The Gambia, in collaboration with USDA-ARS, and other research and development partners. IITA signed a Technology Transfer and Licensing Agreement with BAMTAARE SA for benefiting groundnut and maize value chains. This is the first license to manufacture and distribute an Aflasafe product granted to a private company in Africa. The agreement contemplates full ownership, operation, and management by BAMTAARE and technical support from IITA.